2020
DOI: 10.1186/s12889-020-8370-0
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the relationships between social capital, chronic health conditions and health status among Australian adults: findings from an Australian national cohort survey

Abstract: Background: Social capital is a collective attribute of communities that determines health and well-being of populations. The collective resources in a high social capital community have been reported to result in better health outcomes. While evidence supports the links between social capital and various health outcomes, it is not clear about underlying mechanisms connecting multiple dimensions of social capital to health. Methods: Using the two-wave data from a nationally representative cohort study of Austr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…All variables were rated on 5-point Likert scales (1 = completely disagree/unwilling; 2 = relatively disagree/unwilling; 3 = usually; 4 = relatively agree/willing; 5 = agree/willing). All measurement items were adapted from existing literature [ 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. These items were adjusted, demonstrated and tested in combination with China’s national conditions.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…All variables were rated on 5-point Likert scales (1 = completely disagree/unwilling; 2 = relatively disagree/unwilling; 3 = usually; 4 = relatively agree/willing; 5 = agree/willing). All measurement items were adapted from existing literature [ 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. These items were adjusted, demonstrated and tested in combination with China’s national conditions.…”
Section: Methodsmentioning
confidence: 99%
“… Social Engagement (SE) (5) I often participate in the activities of informal groups (villagers’ associations, interest associations, etc.). [ 45 , 46 ] (6) I often participate in community volunteer activities. (7) I often participate in various activities carried out by the community (health lectures, cultural and sports activities, etc.).…”
Section: Table A1mentioning
confidence: 99%
See 1 more Smart Citation
“…Social capital plays a key role in shaping social and economic outcomes, and research has demonstrated that societies with higher social capital have higher incomes, are less corrupt, are healthier, and function better [ 11 ]. In fact, there is a direct association between social capital and health, with strong social capital correlated with health information sharing among family members and higher self-rated overall health [ 12 , 13 ]. Indeed, social capital has the ability to improve economic efficiency through coordination and cooperation of shared norms to grow entrepreneurial firms, engage in technological advances and enhance strategic alliances [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another research 5 suggests that during an infectious disease epidemic, pregnant women may be particularly distressed because of concerns about their health. Social capital has been suggested to positively impact health status because of its knowledge transfer channels, reinforced behavioral norms, and community cohesion 39 . Recent studies 40 have indicated that community cohesion is linked to the increased use of preventive health care.…”
Section: Discussionmentioning
confidence: 99%